RESPON Akasia mangium DAN Paraserianthes palcataria Leguminocae TERHADAP INOKULASI Rhizobium DALAM HUBUNGANNYA DENGAN KEPADATAN POPULASI Rhizobium TANAH - Suliasih; Sri Widawati (The East Java Biological Society, 1997)
The research aimed to discover the response of the fast growing tree legume to Rhizobium inoculation in relation to the population density of soil Rhizobium (indigenous rhizobia). The density of soil Rhizobium bacteria was predicted based on a plant infection test by using the most probable number (MPN) of soil bacteria. The experimental design used in this work was Completely Randomized Design with factorial provided and 4 replicates. The first factor of treatment were inoculation and uninoculation, and the second factor was soil taken from 5 locations in Cigaru and Jampang-Sukabumi villages. The response of the plant was marked by the increase of dry weigh of leaf, root, and number of root nodules. The result of this study showed that the plants planted in the soil media with < bacteria/gram soil showed more response to inoculation than plants planted in soil media with > 40 bacteria/gram soil.